Spin resonance in the superconducting state of Li1−xFexODFe1−ySe observed by neutron spectroscopy - Davies, N; Rahn, M; Walker, H; Ewings, R; Woodruff, D; Clarke, S; Boothroyd, A (American Physical Society, 2016)
We have performed inelastic neutron-scattering measurements on a powder sample of the superconductor lithium iron selenide hydroxide Li1−xFexODFe1−ySe (x ≈ 0.16, y ≈ 0.02, Tc = 41 K). The spectrum shows an enhanced intensity below Tc over an energy range of 0.64 × 2Δ < E < 2Δ, where Δ is the superconducting gap, and has maxima at the wave vectors Q1 ≈ 1.46 and Q2 ≈ 1.97 °A−1. The behavior of this feature is consistent with the spin-resonance mode found in other unconventional superconductors, and in particular strongly resembles the spin resonance observed in the spectrum of another molecular-intercalated iron selenide Li0.6(ND2)0.2(ND3)0.8Fe2Se2. The signal can be described with a characteristic two-dimensional wave-vector (π,0.67π) in the Brillouin zone of the iron square lattice, consistent with the nesting vector between electron Fermi sheets.